Faktor – Faktor yang Mempengaruhi Index Harga Saham di Jakarta Islamic Index (JII) - Cindi Rahmawati; Wahyu Dwi Warsitasari (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This research is aimed to determine the exchange rate, money in circulation, and the impact of expansion on the stock cost file in the Jakarta Islamic Index (JII) during the observation period of January 2017 to December 2021. Closing price data obtained from the Jakarta Islamic Index (JII) from 2017 to 2021 is the data used as a sample. The method used in this research is a quantitative method using a quantitative approach associative, which aims to determine the effect or relationship between variables. The regression model used in this research is multiple linear regression. This research uses Eviews 9 for data management and purposive sampling for data collection. The results of this research indicate that, partially, inflation does not positively affect the Jakarta Islamic Index (JII) stock price index. On the other hand, the amount of money and the exchange rate in circulation partially harm the stock price index in the Jakarta Islamic Index (JII). In the meantime, the amount of money in circulation, the exchange rate (exchange rate), and simultaneous inflation variables significantly affect the Stock Price Index in the Jakarta Islamic Index (JII) for 2017 to 2020. Keywords : Jakarta Islamic Index (JII), Inflation, Exchange Rate, Money Supply